PT NORTH JAVA SEA GROUP USING MICROSOFT VISUAL BASIC 6.0 - Erdiansyah Wiria Sahputra; Diyah Ruri lrawati, S.Kom, MMSI Diyah Ruri lrawati, S.Kom, MMSI (Jurnal Sistem Informasi, 2006)
Scientific research is aimed to create time-based reservation sistent due on PT NORTH JAVA SEA GROUP, ranging from data input to the preparation of reports using Microsoft Visual Basic 6.0.This research is a scientific research by collecting data. The author obtained these data by conducting interviews on the leaders and relevant employees who worked at the company.From this research we can conclude that by using computerized will gain the ease and speed up the ordering process.